Rational design of temperature swing adsorption cycles for post-combustion CO2 capture. (2nd February 2017) - Joss, Lisa; Gazzani, Matteo; Mazzotti, Marco
Abstract: The design of temperature swing adsorption (TSA) cycles aimed at recovering the heavy product at high purity is investigated by model-based design and applied to the capture of CO2 from flue gases. This model based design strategy and an extensive parametric analysis enables gaining an understanding of how individual steps within TSA cycles affect the achievable purity and recovery of the CO2 product. This insight is used to evaluate three novel TSA cycle configurations by assessing them based on their productivity and energy consumption. The influence of heat integration, cycle scheduling and an external drying step on the performance of the cycles is systematically evaluated. This detailed analysis reveals the importance of the cycle configuration and provides a basis to rationally design TSA cycles for post-combustion CO2 capture. Using a commercial zeolite 13X adsorbent our novel TSA cycle design achieves for the first time CO2 capture and storage specifications (96% CO2 purity and 90% recovery) with moderate heating temperatures of up to 420 K while avoiding the use of compression or vacuum. The specific energy consumption and productivity of this cycle are similar to amine-based absorption processes. The obtained results demonstrate the feasibility of TSA based processes for post-combustion CO2 capture applications, and the presented methodology can be used to evaluate and quantify possible improvements provided by using novel technology elements such as alternative materials. Abstract : Graphical abstract: Abstract : Highlights: Novel TSA cycles achieving high purity and recovery for post-combustion CO2 capture. Effects of flue gas drying, cycle scheduling and heat integration are analyzed. Methodology for a systematic design of TSA cycle configuration and operation. TSA and absorption processes are compared using productivity and energy consumption figures.